Efektivitas Tingkat Pendidikan Orangtua terhadap Prestasi Belajar Siswa Kelas V SD Negeri 067243 Medan Tahun Pelajaran 2025/2026 - Tina Sheba Cornelia; Mawar Br. Sitanggang; Ika Nikita Br. Barus; Marcel Surbakti (Global Education Journal, 2025)
National education is a conscious and planned effort to create a learning environment and process that enables students to actively develop their potential. This study aims to determine the influence of parents' education levels on the academic achievement of Grade V students at SDN 067243 Medan during the 2025/2026 academic year. The issues examined are: (1) What is the profile of parents' education levels? (2) What is the profile of academic achievement? (3) Is there an influence of parents' education levels on academic achievement? This study employs an ex post facto research design. The data analysis methods used include descriptive analysis and an independence test between two factors (chi-square). The population and sample consisted of all 30 Grade V students at SDN 067243 Medan. Data regarding parents' education levels and student academic achievement were obtained through the Grade V homeroom teacher. The results of the independence test yielded a calculated chi-square value of 35.10, which is greater than the table value of 6.49; consequently, the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted, indicating a significant influence of parents' education levels on student academic achievement.